Before the coffee gets cold - Kawaguchi, Toshikazu ([Place of publication not identified] : Hanover Square Press, 2020)
This is a sweet, fable-like tale about a magical seat in a cafe where you can, if you wish, go back in time... An odd read, but also a charming one. A story about human relationships, missed opportunities and the enduring power of love.
Keywords: TIME TRAVEL; OLDER PEOPLE